Pertimbangan Pasar dan Penghargaan Finansial dalam Menentukan Minat Mahasiswa menjadi Akuntan Publik - Montanus K Jeramu; Anim Wiyana (Insan Cita Bongaya Research Journal, 2025)
This study aims to determine and analyze the influence of job market considerations and financial rewards on students' interest in becoming public accountants. This study used a quantitative approach. The study was conducted at STIEM Bongaya. The population in this study was all 171 accounting students from the 2021 intake. The sampling procedure used in this study was saturated sampling. The data source in this study was primary data collected using a questionnaire. The analysis method used was SEM-PLS. The results of this study indicate that job market considerations influence interest in becoming public accountants, and financial rewards influence interest in becoming public accountants.